Burns: learning from the past in order to be fit for the future - Kamolz, Lars-Peter (BioMed Central, 2010)
Many advances have been made in the understanding and treatment of burns. Advances in burn surgery and critical care have decreased mortality and morbidity. Survival from severe burns is no longer the exception, but unfortunately death still occurs. Williams and colleagues have determined in their recent paper the predominant causes of death in order to develop new treatment avenues and future trajectories suitable to increase survival and overall outcome. A lot of burn deaths may be preventable with better airway management and a more precise and adequate volume management, but the leading cause of death in patients suffering from severe burns, which has to be faced, is sepsis. Sepsis due to multidrug-resistant organisms will continue to impede efforts to increase survival, and new strategies that go beyond the surgical and clinical techniques, which are already implemented, have to be developed in order to fight these organisms and their related complications.